Research on the dissemination and evolution of the traditional ethnic sport culture - Xiangkui Chen; Tao Yang; Zhaojin Li, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The basic aim of this research study is to describe the dissemination of evolution related to the traditional ethnic sport culture. This research study depends on theoretical base analysis to determine the research used different websites linked to dissemination and evolution. The data collected related to the traditional ethnic sport culture research study based on theory and some data based on primary research. For this purpose, data collected through questions for measuring the research used smart PLS software, and run results included significant analysis and smart PLS Algorithm model related to the traditional ethnic sport culture. In conclusion, sports are cultural in a variety of ways. Participating in sports enables us to have and share culture, keeping us physically fit and healthy and enhancing our reputation via success. Furthermore, Sports help us develop a sense of self and community. Even better, we can introduce people to our culture. Sports participation is one of the few ways we can interact with and learn about another culture. Recognizing this fact enables us to use sports for good.